2016
DOI: 10.1016/j.bbr.2016.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Rat exposure in mice with neuropathic pain induces fear and antinociception that is not reversed by 5-HT2C receptor activation in the dorsal periaqueductal gray

Abstract: Previous studies have demonstrated that serotonin 5-HT2C receptors in the dorsal periaqueductal gray (dPAG) mediate both anxiety and antinociception in mice submitted to the elevated plus maze. The present study examined the effects of intra-dPAG infusion of the serotonin 5-HT2C receptor agonist (MK-212) in the defensive reactions and antinociception in mice with neurophatic pain confronted by a predator. Neuropathic pain was induced by chronic constriction injury (CCI) of the sciatic nerve, and predator confr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…The involvement of the PAG 5-HT 2C receptors in the modulation of pain response has been previously emphasized (Baptista-de-Souza et al, 2014;de Freitas et al, 2014;Furuya-da-Cunha et al, 2016;Obata et al, 2007). Thus, aiming to better characterize the role of the dPAG 5-HT 2C receptor in the modulation of OAA, we injected 0.1 nmol of SB 242084 (a dose without intrinsic effects on nociceptive response; see results of Exp.…”
Section: Discussionmentioning
confidence: 99%
“…The involvement of the PAG 5-HT 2C receptors in the modulation of pain response has been previously emphasized (Baptista-de-Souza et al, 2014;de Freitas et al, 2014;Furuya-da-Cunha et al, 2016;Obata et al, 2007). Thus, aiming to better characterize the role of the dPAG 5-HT 2C receptor in the modulation of OAA, we injected 0.1 nmol of SB 242084 (a dose without intrinsic effects on nociceptive response; see results of Exp.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, many studies have demonstrated that the analgesia induced by stimulation of the PAG is related to areas with a high concentration of serotonergic receptors (Lohof et al, 1987;Coimbra and Brandao, 1997;Brandao et al, 1999;Zhang et al, 2000;Lu et al, 2010). In this sense, we have previously reported the role of 5-HT 1A and 5-HT 2C receptors in reverse and accentuate, respectively, the fear-induced antinociception in mice (Baptista et al, 2012;Furuya-da-Cunha et al, 2016;Tavares et al, 2018).…”
mentioning
confidence: 62%
“…These results suggest that (i) 5-HT may facilitate nociception INTRODUCTION Serotonin (5-HT) is involved in the etiology of numerous disease states, including depression, anxiety, panic disorders and painful conditions (Richardson, 1990;Supornsilpchai et al, 2006;Artigas, 2013a;Zangrossi and Graeff, 2014). The 5-HT receptors belong to the G-protein-coupled receptor superfamily (except for the 5-HT3 receptor, which is a ligand-gated ion channel) with at least 14 distinct members (Hoyer et al, 2002), however, the role of 5-HT 1A and 5-HT 2C receptor subtypes in the modulation of emotional and pain responses have been more extensively studied (Zanoveli et al, 2010;Strauss et al, 2013;Baptista-de-Souza et al, 2014;Furuya-da-Cunha et al, 2016).…”
mentioning
confidence: 99%
“…The effects of 5-HT1 receptors on the modulation of nociception have been widely studied [43,44]; however, it is required to obtain exact data on the antinociceptive activities of 5-HT2 areas [34]. Nonetheless, 5-HT2 receptors are possibly involved in the antinociceptive impacts of periaqueductal grey stimulation and stress [45].…”
Section: Discussionmentioning
confidence: 99%